Modulation of non-spatial attention and the global/local processing bias - Van Vleet, Thomas M. (2010)
Amelioration of the rightward spatial attention bias in patients with hemispatial neglect following manipulations of non-spatial attention suggests that spatial attention and mechanisms related to the regulation of attention are interrelated. Studies in normal, healthy subjects have shown similar modulation in spatial bias following tonic and phasic changes in attention suggesting that this interaction is a general mechanism of attention rather than a curiosity of the neglect disorder. The current study examined this attentional interaction to determine if perceptual processes favoring one hemisphere over the other are affected by this relationship. Participants first made rapid discriminations of Navon figures presented at central fixation. As expected, when participants attended to either the local or global dimension, incongruence in the orthogonal dimension resulted in longer reaction times for accurate discrimination compared to congruent trials. However, following a brief (16-min) continuous performance task designed to elicit behaviors associated with greater tonic and phasic alertness, participants showed significantly less local interference when attending the global dimension and more global interference when attending the local dimension on the Navon discrimination task compared to a control task condition. The results indicate that exercising tonic and phasic alertness produces a global processing bias.